Cognitive Behavioral Counseling to Overcome Anxiety Facing Exams: A Quasi-Experimental Study on SMA Negeri 2 Pagaden Students - Siti Nuriah; Muhammad Adzroi; Ahman Ahman; Irfan Fahriza; Tea Septina (Journal of Education and Counseling (JECO), 2024)
This research aimed to produce cognitive behavioral counseling services which are effective to help students overcome anxiety in facing the exam. The research used a quantitative approach and quasi-experimental research design nonequivalent pretest-posttest control group design. The research was conducted at SMA Negeri 2 Pagaden with the first semester students were taken randomly as research subject. The research instrument that was used was Anxiety Scale in facing exam. The results showed empirically, a cognitive behavioral counseling intervention has proven effective to overcome anxiety in students